Characteristics of Bone Gelatin Tilapia (Oreochromis niloticus) Processed by Using Hydrolysis With Phosphoric Acid and Papain Enzyme - Gugun Hidayat; Eko Nurcahya Dewi; Laras Rianingsih (Jurnal Pengolahan Hasil Perikanan Indonesia, 2016)
Phosphoric acid and papain enzyme able to hydrolyzing collagen from Tilapia into gelatin . Thepurpose of this research was to determine the best concentration of phosphoric acid and papain enzymeand to determine the physicochemical characteristic gelatin to from Tilapia fish bone which processedwith phosphoric acid and papain enzyme. The first research phase was making bone gelatin tilapia usingphosphoric acid at concentration of 4%, 5% and 6%, and the papain enzyme 0.5%, 1% and 1.5%. Thesecond phase was characterize the physicochemical gelatin from the best concentration of phosphoric acidconcentration (6%) and papain enzyme (1.5%), all treatment done with three repetitions. Analysis of thedata using ANOVA with completely randomized (CRD) design If there was difference between treatmentthen continued with Honestly Significant Difference Test (HSDT). The results of the first research phasefound the best concentration were 6% of phosphoric acid and 1.5% papain enzyme, its shows by the valuegel strength 325,95 and 373,32 g.bloom. The second research phase shows that the the best results obtainedin this study was gelatin from 1.5% papain enzyme as hydrolysis agent, the physicochemical characteristicwere: 376.21 g.bloom gel strength; viscosity of 7.57 cP; yield 6.30%; protein content of 86.46%; water contentof 7.12%; and the pH value of 5.11.Keywords : gelatin, hydrolysis, papain enzyme, phosphoric acid, tilapia bones